Comprehensive Study of Pediatric Dentistry, Quality Assurance, and Dental Education for Future Practitioners - Alqarni, Malikah Mohammed; Aldrees, Shaden Saleh (Journal of Ecohumanism, 2024)
Children’s dentistry is highly important because the disease can have a profound impact on their comfort, health, and general well-being. Dental healthcare has increasingly adopted the focus that output quality needs to be achieved and sustained while dental education is adjusting itself to produce competent clinicians to address future clinical needs. This paper aims to describe the roles that pediatric dentistry, quality assurance, and dental education play with regard to clinical practice effectiveness and preparedness for practitioners. As part of this mixed-method study, the current paper explores the efficiency of QA systems, how educational training is lacking in them, and how future dentists are prepared to handle pediatric clients. They further reveal that strong QA had a positive influence on care quality, professional performance, and practice, as well as that tailored educational interventions were also effective in the given context. Suggested changes involve the assimilation of updated forms of quality assurance, changes in courses to focus on pediatric medicine, as well as support for interprofessional training programs.